Ответ:
Пошаговое объяснение:
№1
2/3 : (4/9х - 4/9) + 1/20 = 4/5
2/3 : (4/9х - 4/9) = 4/5 - 1/20
2/3 : (4/9х - 4/9) = 16/20 - 1/20
2/3 : (4/9х - 4/9) = 15/20
4/9х - 4/9 = 2/3 : 15/20
4/9х - 4/9 = 2/3 * 20/15
4/9х - 4/9 = 40/45
4/9х - 4/9 = 8/9
4/9х = 8/9 + 4/9
4/9х = 12/9
х = 12/9 : 4/9
х = 12/9 * 9/4
х = 12/4
х = 3
№2
5/7 : (6/7х + 3/7) - 1/2 = 1/6
5/7 : (6/7х + 3/7) = 1/6 + 1/2
5/7 : (6/7х + 3/7) = 1/6 + 3/6
5/7 : (6/7х + 3/7) = 4/6
6/7х + 3/7 = 5/7 : 4/6
6/7х + 3/7 = 5/7 * 6/4
6/7х + 3/7 = 30/28
6/7х = 30/28 - 3/7
6/7х = 30/28 - 12/28
6/7х = 18/28
х = 18/28 : 6/7
х = 18/28 * 7/6
х = 3/4 * 1/1
х = 3/4
№3
3/4 : (5/8х - 1/2) - 1/8 = 1/4
3/4 : (5/8х - 1/2) = 1/4 + 1/8
3/4 : (5/8х - 1/2) = 2/8 + 1/8
3/4 : (5/8х - 1/2) = 3/8
5/8х - 1/2 = 3/4 : 3/8
5/8х - 1/2 = 3/4 * 8/3
5/8х - 1/2 = 1/1 * 2/1
5/8х - 1/2 = 2/1
5/8х - 1/2 = 2
5/8х = 2 + 1/2
5/8х = 2. 1/2
х = 2. 1/2 : 5/8
х = 5/2 * 8/5
х = 40/10
х = 4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Пошаговое объяснение:
№1
2/3 : (4/9х - 4/9) + 1/20 = 4/5
2/3 : (4/9х - 4/9) = 4/5 - 1/20
2/3 : (4/9х - 4/9) = 16/20 - 1/20
2/3 : (4/9х - 4/9) = 15/20
4/9х - 4/9 = 2/3 : 15/20
4/9х - 4/9 = 2/3 * 20/15
4/9х - 4/9 = 40/45
4/9х - 4/9 = 8/9
4/9х = 8/9 + 4/9
4/9х = 12/9
х = 12/9 : 4/9
х = 12/9 * 9/4
х = 12/4
х = 3
№2
5/7 : (6/7х + 3/7) - 1/2 = 1/6
5/7 : (6/7х + 3/7) = 1/6 + 1/2
5/7 : (6/7х + 3/7) = 1/6 + 3/6
5/7 : (6/7х + 3/7) = 4/6
6/7х + 3/7 = 5/7 : 4/6
6/7х + 3/7 = 5/7 * 6/4
6/7х + 3/7 = 30/28
6/7х = 30/28 - 3/7
6/7х = 30/28 - 12/28
6/7х = 18/28
х = 18/28 : 6/7
х = 18/28 * 7/6
х = 3/4 * 1/1
х = 3/4
№3
3/4 : (5/8х - 1/2) - 1/8 = 1/4
3/4 : (5/8х - 1/2) = 1/4 + 1/8
3/4 : (5/8х - 1/2) = 2/8 + 1/8
3/4 : (5/8х - 1/2) = 3/8
5/8х - 1/2 = 3/4 : 3/8
5/8х - 1/2 = 3/4 * 8/3
5/8х - 1/2 = 1/1 * 2/1
5/8х - 1/2 = 2/1
5/8х - 1/2 = 2
5/8х = 2 + 1/2
5/8х = 2. 1/2
х = 2. 1/2 : 5/8
х = 5/2 * 8/5
х = 40/10
х = 4